Improving Team Effectiveness of College Student Association of Science and Technology Innovation at Zhanjiang University of Science and Technology in China - Chen, Yingjian; Ruckthum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study aimed to explore pathways to enhance the team effectiveness of college student association and examine their impacts on student development. Focusing on the College Student Association of Science and Technology Innovation (CSASTI) at Zhanjiang University of Science and Technology (ZUST), the research employed Organizational Development Intervention (ODI) to improve communication, innovation, incentive, and leadership skills to enhance team effectiveness. A mixed-methods approach was adopted, combining questionnaire surveys and semi-structured interview, with a sample of 40 students participating in a three-month intervention. During the intervention, four targeted workshops were conducted, including the fishbowl conversation workshop for communication, the skills training workshop for innovation, the goal setting workshop for incentive, and the appreciative inquiry workshop for leadership skills. Data analysis revealed significant differences in all five variables before and after the ODIs, indicating that targeted ODI strategies could effectively improve team effectiveness. The findings suggest that by optimizing communication mechanisms, fostering innovative thinking, refining incentive systems, and strengthening leadership skills, the student association can not only increase operational team effectiveness but also better support student growth and development. This study provides practical insights and a feasible framework for improving the management of college student associations.